PENGARUH PENGETAHUAN AKUNTANSI, KOMITMEN ORGANISASI, KARAKTERISTIK WIRAUSAHA DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KINERJA MANAJERIAL PADA “COFFEE SHOP” DI BANDAR LAMPUNG - febby fadlika syabila; Reni Oktavia; Chara Tidespania Tubarat (Jurnal Akuntansi dan Keuangan (JAK), 2021)
Currently, coffee shops or commonly known as coffee shops are not foreign to the ears. For in Bandar Lampung itself there are lots of coffee shops ranging from lower class to upper class. Various types of consumers make business competition something that must be considered for entrepreneurs in running and maintaining their business. The purpose of this study is to determine the effect of accounting knowledge, organizational commitment, environmental uncertainty and entrepreneurial characteristics on managerial performance at a coffee shop in Bandar Lampung. The research method used is causal associative research, namely research that aims to analyze the relationship between a variable with other variables. The sampling technique used in this study is a sampling technique with purposive sampling method. Methods of data collection using observation and questionnaires. The result of this research is that there is a positive influence between accounting knowledge, organizational commitment and entrepreneurial characteristics on managerial performance.